Analisis Sosial Ekonomi Dampak Pernikahan Dini Dikalangan Remaja - Junita Friska; Diana Agatha Nainggolan; Ira Syafitri Siregar; Ismaina Hamda Siregar; Sri Dina Br Purba; Theresia Agustine Tuka (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Marriage is an institution that binds two individuals in a relationship officially recognized religion, law and customs. This becomes the foundation important in building a happy family life and sustainable. However, early marriage, especially under the age of 20, poses serious challenges. Teenagers often marry too young not ready to handle the responsibilities of marriage and the risks of experiencing health and economic problems. This problem occurs throughout Indonesia, reflects the complexity of social and economic problems. The need for action strong preventive and intervention to overcome early marriage and improve community welfare. Qualitative descriptive research uses an interview approach and data analysis. Combining qualitative methods, this research explores socio-economic factors that influence early marriage. The aim is to provide a holistic understanding for more effective development policies. Early marriage has a serious impact on individuals and society, influenced by social, economic factors and parental influence. Children or teenagers who marry at a young age are at risk of facing health, educational and economic problems, poverty and gender inequality. Steps such as upgrading education, women's empowerment, and economic development It is necessary to reduce early marriage and deal with its impacts appropriately.